Tren Perjudian Online di Kalangan Mahasiswa: Dampak, dan Upaya Pencegahannya - Agnes Chintya Siringoringo; Sri Yunita; Jamaludin Jamaludin (Journal on Education, 2024)
Online gambling has become a prominent phenomenon among students because it is considered a fast way to earn money instantly, even becoming the main source of income for some students to meet their daily needs. However, serious attention to this phenomenon arises because it is considered detrimental to the future of Indonesia's young generation, changing mindsets in earning a living and forming less productive personalities. Some cases involve students using money from their tuition fees to gamble without considering the risks, potentially threatening their ability to pay off educational costs. Therefore, this research aims to identify the factors driving students to engage in online gambling. Factors such as social, economic, situational aspects, learning environment, perception of winning, and perception of addiction influence students' tendencies in online gambling, while secretive attitudes, difficulty accepting advice, stubbornness, and reluctance to admit or avoid potential dangers are obstacles in dealing with this phenomenon.